2018
DOI: 10.1101/gad.318709.118
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by the stress-activated MAPK Slt2 down-regulates the yeast TOR complex 2

Abstract: Saccharomyces cerevisiae target of rapamycin (TOR) complex 2 (TORC2) is an essential regulator of plasma membrane lipid and protein homeostasis. How TORC2 activity is modulated in response to changes in the status of the cell envelope is unclear. Here we document that TORC2 subunit Avo2 is a direct target of Slt2, the mitogenactivated protein kinase (MAPK) of the cell wall integrity pathway. Activation of Slt2 by overexpression of a constitutively active allele of an upstream Slt2 activator (Pkc1) or by auxin-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 82 publications
4
50
0
Order By: Relevance
“…The C-terminus of Avo1 contains a Pleckstrin homology (PH) domain that binds PI(4,5)P 2 and mediates the plasma membrane anchoring of TORC2 (Berchtold and Walther 2009). Avo2 is a relatively small subunit essential for cell survival during stress conditions (Leskoske et al 2018). Bit61 also binds to TORC2 but its role remains unknown (Loewith et al 2002).…”
Section: Mct Assembly and Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminus of Avo1 contains a Pleckstrin homology (PH) domain that binds PI(4,5)P 2 and mediates the plasma membrane anchoring of TORC2 (Berchtold and Walther 2009). Avo2 is a relatively small subunit essential for cell survival during stress conditions (Leskoske et al 2018). Bit61 also binds to TORC2 but its role remains unknown (Loewith et al 2002).…”
Section: Mct Assembly and Organizationmentioning
confidence: 99%
“…MCT-MCW -In both fission and budding yeast, cell wall stress results in activation of CWI pathway that negatively regulates the growth-promoting functions of MCT (Cohen, Kupiec and Weisman 2014;Leskoske et al 2018). Recently, it was shown that activation of either CWI via Pkc1 or the HOG pathway resulted in the phosphorylation of the Avo2 subunit of TORC2 by the mitogen-activated protein kinase Slt2, leading to the down-regulation of TORC2 activity (Leskoske et al 2018).…”
Section: Mcc-mct -mentioning
confidence: 99%
“…Basal activity and stability of Ypk1 also requires its phosphorylation at S644, which lies within a conserved sequence (dubbed the "turn motif") located downstream of its kinase homology domain within a C-terminal regulatory domain [16]. This modification is installed by TORC2, which is also largely PM-associated [17][18][19][20][21]. Under certain stressful conditions that stimulate TORC2-mediated phosphorylation of Ypk1, such as sphingolipid limitation [22], heat stress [23], hypotonic conditions [24,25], and acetic acid stress [26], TORC2 further elevates Ypk1 activity by phosphorylating four additional sites in its C-terminal regulatory domain, paramount among them is T662, which lies within another conserved sequence (dubbed the "hydrophobic motif") in the C-terminal domain [13,16].…”
Section: Background and Overviewmentioning
confidence: 99%
“…Phosphorylation of Ypk1 at these locations further enhances both its activity and stability. Under other stressful conditions, such as hypertonic shock [27,28], treatments that damage the cell wall [19], and treatments that decrease "membrane tension" [29], TORC2-mediated phosphorylation of Ypk1 is dramatically reduced.…”
Section: Background and Overviewmentioning
confidence: 99%
See 1 more Smart Citation